Randomised controlled study comparing two psychological therapies for Posttraumatic Stress Disorder (PTSD): Emotional Freedom Techniques (EFT) vs. Narrative Exposure Therapy (NET) - AlHadethe, Ashraf; Hunt, Nigel; Ghaffar, Al-Qaysi; Thomas, Shirley A. (SciTechnol, 2015)
Background: Post-Traumatic Stress Disorder (PTSD) is a common psychological reaction after traumatic events. The aim of this study was to evaluate the efficacy of Emotional Freedom Techniques (EFT) and Narrative Exposure Therapy (NET) as treatments for PTSD with traumatised people.